Effectiveness of Traditional Chinese Medicine-Based Acupuncture Therapy in Managing Myoclonus in Generalized Dystonia: A Case Report - J. Anbudasan; V. Kavitha; M.R. Monicaasun; N. Prabu; A. Mooventhan (Journal of Acupuncture Research)
Dystonia is a neurological disorder characterized by abnormal involuntary muscle contractions. This study aimed to determine the effect of acupuncture on a 26-year-old male patient with idiopathic generalized dystonia. For the past 5 years, the patient had involuntary muscle contractions, abnormal and painful posture of the right upper limb, and slurred speech. He was taking anticholinergic medication benzhexol (trihexyphenidyl hypochloride) and vitamin B complex from disease onset. At our hospital, he underwent three courses of acupuncture (one course consisted of 20 minutes of acupuncture/day daily for 15 days followed by no intervention for 15 days) for 3 months. The intensity of myoclonus decreased from day 1 and ceased from day 5 of the intervention. In addition, myoclonus did not recur at the 1-month follow-up even without acupuncture. Thus, 3 months of acupuncture was found to effectively reduce the incidence of myoclonus in a patient with generalized dystonia.